SUBSAMPLING TO TWO PROBATION WITH PRIMARY UNITS OF UNEQUAL SIZES - Péllico Netto, Sylvio (1996)
This paper deals with the methodology of sampling allocation in forest stratification. The criteria used for the allocation includes the participation of stands inside a stratum as part of the sampling procedure, known in the literature as “Subsampling  With Units of Unequal Sizes”. The efficiency of this applied methodology was considered due to the stand’s size variation and, consequently, doing to the subsampling allocation with selection proportional to their sizes. The results of this procedure showed very promising and appropriated to be used in continuos forest inventories.